ANALISIS KESEIMBANGAN TINGKAT SUKU BUNGA DAN GDP DI INDONESIA : TINJAUAN INTERAKSI KEBIJAKAN FISKAL DAN MONETER (1998 – 2011) - Vietha Devia (Quantitative Economics Journal, 2016)
The aim of this study is to see how the equlibrium (internal balance) of interest rate and GDP created by the goods market (IS curve) and money market (LM). Then from the earlier internal balance, the study want to see how the fiscal and monetary policy affects the economy, particularly in influencing the internal balance when the two policies were interacted. The study was conducted with Two Stage Least Square (TSLS) method to finding IS – LM equation using time series data (1998 – 2011). Then do the trial and error to find an internal balance. After that the authors try to find the shift of IS – LM when there were policy intervention. The result showed that the earlier of internal balance is 7,79% for interest rate, and Rp. 438.011 billion for GDP. Based on estimation of time series data, the study concluded that, there is no equilbrium for internal balance when fiscal and monetary policy were interacted. When there is fiscal policy intervention, the result show that the policy effectively affect economic growth. While when there is monetary policy intervention, the result show that the economy not responsive to the policy. So when the fiscal and monetary policy were interacted, it can not be created the new equlibrium (internal balance).